DEPICTING EFL LEARNERS' STRATEGIES AND DILEMMA IN TRANSLATION - Afif Ikhwanul Muslimin; Fitrana Harintama (Institut Agama Islam Negeri (IAIN) Manado, 2022)
Depicting EFL Learners' Strategies and Dilemma in Translation. The present study isaimed at depicting EFL learners? strategies and dilemma in conducting English-Indonesia translations. This study will employ survey design with quantitativeapproach. The participants will be 124 EFL learners who are joining translation classat English Education Department, UIN Mataram in academic year 2021/2022. Theadapted questionnaire comprises translation problems in terms of vocabulary,culture understanding, choice of strategy, grammar and specific field of study will beadministered to participants. Furthermore, the collected data will be analyzedstatistically, portrayed into charts, and discussed with existed theories. The result ofthe research showed that all strategies (Newmark, 1988) were applied by students.However, the most dominant strategies used were recognized translation,transference, functional equivalent, synonymy, and shifts. Similar to the analysis onthe EFL students? dilemma in translation, students experienced five dilemmas suchas facing difficulty to choose best strategy to translate, owning limited vocabulary,getting difficult in matching SL and TL grammar, lacking of culture understanding,and being unable to know the translation of specific term in different field. Thelowest frequency of students? acknowledgement on the dilemma was about theunderstanding on TL culture.Keywords: Translation; EFL learners; dilemma; Indonesia